2016
DOI: 10.1016/j.matchar.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure and residual stress during annealing of austenitic and ferritic steels

Abstract: In this work the recovery and recrystallization processes occurring in ferritic and austenitic steels were studied. To determine the evolution of residual stresses during material annealing the nonlinear sin 2 ψ diffraction method was used and an important relaxation of the macrostresses as well as the microstresses was found in the cold rolled samples subjected to heat treatment. Such relaxation occurs at the beginning of recovery, when any changes of microstructure cannot be detected using other experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…With our thermal treatment, the initial tempered martensitic structure converted -at least partly-to austenite when the samples were heated at 1050°C for 1 hour. Moreover, Wawszczak et al [66] showed that the microstructure of a ferritic-martensitic steel (compositions close to those obtained for P92) does not change significantly after annealing at temperature below 400°C. In this range of temperatures, the Al coating cannot be formed.…”
Section: -Metallurgical Evolutions Induced By the Aluminisation Promentioning
confidence: 66%
See 1 more Smart Citation
“…With our thermal treatment, the initial tempered martensitic structure converted -at least partly-to austenite when the samples were heated at 1050°C for 1 hour. Moreover, Wawszczak et al [66] showed that the microstructure of a ferritic-martensitic steel (compositions close to those obtained for P92) does not change significantly after annealing at temperature below 400°C. In this range of temperatures, the Al coating cannot be formed.…”
Section: -Metallurgical Evolutions Induced By the Aluminisation Promentioning
confidence: 66%
“…9. In order to recover the initial microstructure of this steel, after a rapid quench in air a subsequent annealing shall be performed at 760°C for 1 hour [66]. Nevertheless, the aluminisation realized in this study was done in a tubular furnace which is not able to cool down quickly.…”
Section: -Metallurgical Evolutions Induced By the Aluminisation Promentioning
confidence: 99%
“…At this temperature, we are operating in the recovery regime of the material, because no nucleation of new grains was observed. Wawszczak et al determined the recovery regime for ferritic steels at temperatures lower than 400°C and the recrystallization temperature for temperatures above 600°C, whilst calorimetric experiments show an exothermic peak at 500°C [10]. In the recovery regime, no changes in EBSD mapping and microstructure were observed, however during recrystallization there were modifications; recrystallization depend significantly on the stacking fault energy [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, residual stresses are solely due to heat treatment because the residual stresses resulting from the rolling process are eliminated during an annealing treatment at 1100°C [14,15]. Thereafter, quenching and tempering are applied.…”
Section: Experimental Determination Of the Residual Stresses Induced mentioning
confidence: 99%
“…4). Wawszczak et al [15] found that, after rolling, the residual stresses in a 316L plate in the rolling and transversal directions are not identical. However, the neutron diffraction results show that the residual stresses follow the same distribution in both the X and Y directions.…”
Section: Residual Stressmentioning
confidence: 99%